1992
DOI: 10.1148/radiology.183.2.1561354
|View full text |Cite
|
Sign up to set email alerts
|

Detection of subtle microcalcifications: comparison of computed radiography and screen-film mammography.

Abstract: Observer performance tests were conducted to compare the effects of image-processing technique (unsharp mask filtering) on the diagnostic accuracy of computed radiography (CR) with storage phosphors in the detection of microcalcifications. Comparison of detectability of microcalcifications with CR and with screen-film mammography was also performed. Clusters of microcalcifications (125-250 microns in diameter) were randomly superimposed on human breast specimens. Observer performance tests were carried out wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Some studies have not shown significant differences between computed tomography and conventional technique [2,3,5,7], whereas others have shown better results for the conventional technique [5,9]. Even if some results did not indicate any differences, artefacts on the digital mammograms were sometimes misjudged as microcalcifications [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have not shown significant differences between computed tomography and conventional technique [2,3,5,7], whereas others have shown better results for the conventional technique [5,9]. Even if some results did not indicate any differences, artefacts on the digital mammograms were sometimes misjudged as microcalcifications [2].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of digital mammography [2±7] have shown no significant differences between digital and screen-film techniques. Some studies [8,9], however, have reported inferior results for the digital technique compared with the screen-film technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique is frequently used in medical radiology to evaluate diagnostic image quality and provides two radiographs simultaneously with a single exposure. 11,12 It has been proved that the technique offers single-exposure imaging with only nominal degradation in film and SPP image quality, relative to the two standard image counterparts and, therefore, has been adopted as the method of choice in the present study to avoid the added radiation exposure to patients. 13,14 After exposure, films were processed in an automatic processor (XR 24; Dü rr, Bietigheim, Germany) while phosphor plates were read on a Digora PCT laser scanner.…”
Section: Clinical Radiographsmentioning
confidence: 99%
“…As for image quality, the accuracy of CR reading is affected by the image-processing parameters and windowing [7,8,9]. Kallergi et al [10] reported that interobserver variation in the digitized mammogram reading (105-µm pitch, 12-bit gray scale) was greater than in the film reading.…”
Section: Discussionmentioning
confidence: 99%